Strengthening the pipeline of Aboriginal and Torres Strait Islander doctors into and through general practice training in Queensland, Australia: a scoping review - Dominic Orih; Robyn Grigg; James Flynn; Bradley Murphy (Frontiers in Medicine, 2026)
Background Aboriginal and Torres Strait Islander peoples experience significant health disparities relative to non-Indigenous Australians. Notwithstanding growing policy recognition of the link between Aboriginal and Torres Strait Islander health professionals and improved community health outcomes, their representation remains below parity in medical practice. This is particularly evident in general practice, where the general practitioner (GP) workforce shortfall intensifies nationally, and GP roles have become the hardest to fill across Aboriginal Community Controlled Health Organisations. This scoping review maps the evidence on strategies, programs, and frameworks for strengthening their participation, focusing on Queensland, where Aboriginal and Torres Strait Islander peoples form a comparatively large and geographically dispersed population. Methods We followed the PRISMA Extension for Scoping Reviews (PRISMA-ScR) and the Joanna Briggs Institute methodology. Six databases (PubMed, CINAHL EBSCOhost, Scopus, Google Scholar, ProQuest, and Informit Indigenous Collection) and grey literature were searched, restricted to 2016–2026; one earlier eligible source from 2007 was retained via reference-list searching. After duplicate removal and staged screening, 27 sources were synthesised narratively across four domains: workforce data, programs and initiatives, international evidence, and barriers, enablers, and cultural safety frameworks. Results Synthesis yielded five findings: (i) persistent underrepresentation despite sustained policy attention; (ii) cultural unsafety and racism as structural drivers of attrition; (iii) Indigenous self-determination in governance as a prerequisite for effectiveness; (iv) a financing gap indicating inadequate funding sustainability and disincentives at the hospital-to-general practice transition; and (v) a design gap between discrete interventions and the pipeline needed to address inequity at scale. Programs including the Indigenous General Practice Trainee Network, Joint Colleges Training Services, the Australian Indigenous Doctors' Association Specialist Trainee Support Program, the Royal Australian College of General Practitioners' Yagila Wadamba program, and the Remote Vocational Training Scheme, alongside Canadian and New Zealand models, offer transferable lessons. Conclusion Strengthening the Aboriginal and Torres Strait Islander general practice pipeline in Queensland requires a longitudinal strategy combining culturally safe training, Aboriginal and Torres Strait Islander-led governance, sustainable multi-year funding, remuneration reform, and enhanced longitudinal data. Targeted action across every pipeline stage is needed to achieve workforce parity and improve outcomes in underserved communities.